2006
DOI: 10.1603/0022-2585(2006)43[647:iopsfo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phlebotomine Sand Flies on U.S. Military Operations at Tallil Air Base, Iraq: 1. Background, Military Situation, and Development of a “Leishmaniasis Control Program”

Abstract: One of the most significant modern day efforts to prevent and control an arthropod-borne disease during a military deployment occurred when a team of U.S. military entomologists led efforts to characterize, prevent, and control leishmaniasis at Tallil Air Base (TAB), Iraq, during Operation Iraqi Freedom. Soon after arriving at TAB on 22 March 2003, military entomologists determined that 1) high numbers of sand flies were present at TAB, 2) individual soldiers were receiving many sand fly bites in a single nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…Important vector species (e.g., P. papatasi and P. alexandri) are abundant from April to October in all sites that were examined. Although we have not presented results from testing of sand ßies for leishmaniasis in this paper, our data suggest that Leishmania parasites are present in a signiÞcant (Ͼ1%) proportion of sand ßies at TAB (Coleman et al 2006). In the absence of a vaccine or chemoprophylactic drugs, the best method of protection against leishmaniasis remains a combination of a sand ßy control and effective use of personal protective measures.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Important vector species (e.g., P. papatasi and P. alexandri) are abundant from April to October in all sites that were examined. Although we have not presented results from testing of sand ßies for leishmaniasis in this paper, our data suggest that Leishmania parasites are present in a signiÞcant (Ͼ1%) proportion of sand ßies at TAB (Coleman et al 2006). In the absence of a vaccine or chemoprophylactic drugs, the best method of protection against leishmaniasis remains a combination of a sand ßy control and effective use of personal protective measures.…”
Section: Discussionmentioning
confidence: 70%
“…The abundance of the sand ßies was reßected in the high number of bites received by U.S. military personnel stationed at TAB. In 2003, up to 75% of soldiers in certain units reported receiving insect bites, with a number of soldiers receiving an estimated 1,000 or more bites in a single night (Coleman et al 2006). Examination of the bites, interviews with the soldiers, and collection of biting arthropods in areas where bites occurred all suggested that sand ßies were responsible for almost all of these bites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…major in this region is the great gerbil, Rhombomys opimus (Rodentia: Muridae), other rodents can be infected with the parasite (Nadim et al, 1979). Since the deployment of international military forces to Iraq and, subsequently, to Afghanistan, hundreds of the soldiers involved have developed zCL (Coleman et al, 2006;Faulde et al, 2006). Appropriate preventive schemes based on monitoring and control need to include sandfly trapping, assessments of the prevalences of infection in local sandflies, reduction in the numbers of potential breeding sites for the vector species, and personal protection against sandfly bites .…”
mentioning
confidence: 99%